(y-9)(y+3)=0

Simple and best practice solution for (y-9)(y+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-9)(y+3)=0 equation:


Simplifying
(y + -9)(y + 3) = 0

Reorder the terms:
(-9 + y)(y + 3) = 0

Reorder the terms:
(-9 + y)(3 + y) = 0

Multiply (-9 + y) * (3 + y)
(-9(3 + y) + y(3 + y)) = 0
((3 * -9 + y * -9) + y(3 + y)) = 0
((-27 + -9y) + y(3 + y)) = 0
(-27 + -9y + (3 * y + y * y)) = 0
(-27 + -9y + (3y + y2)) = 0

Combine like terms: -9y + 3y = -6y
(-27 + -6y + y2) = 0

Solving
-27 + -6y + y2 = 0

Solving for variable 'y'.

Factor a trinomial.
(-3 + -1y)(9 + -1y) = 0

Subproblem 1

Set the factor '(-3 + -1y)' equal to zero and attempt to solve: Simplifying -3 + -1y = 0 Solving -3 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1y = 0 + 3 -1y = 0 + 3 Combine like terms: 0 + 3 = 3 -1y = 3 Divide each side by '-1'. y = -3 Simplifying y = -3

Subproblem 2

Set the factor '(9 + -1y)' equal to zero and attempt to solve: Simplifying 9 + -1y = 0 Solving 9 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1y = 0 + -9 -1y = 0 + -9 Combine like terms: 0 + -9 = -9 -1y = -9 Divide each side by '-1'. y = 9 Simplifying y = 9

Solution

y = {-3, 9}

See similar equations:

| -2(-7n+6)-2(8n+1)=-22 | | f+50=97 | | 3(6-2x)=8x | | 5y^2-27y+10=0 | | 2x+3=34 | | -5g=-20 | | 4.8x+0.2(x-2)=3 | | x^2-16x+9=-4x-2 | | 4x-10=-2x+14 | | 15z^2+16z+4=0 | | 6x+10+14x=5(1+4x) | | 4x+4 -6x=8(x-2) | | 268=69-w | | -8n=80 | | 8x+4y+6=70 | | 2z+5=3z | | -10x+16=-2(5x-8) | | 2x(x+2)=3(x+2) | | 2x^3+9x^2-8x-36=0 | | 23-16=6x-2x+9x | | -6+3Y=3+2Y | | 12z^2-17z-5=0 | | 5x-2=x+85 | | 12x^2-17z-5=0 | | z-6z=9z-6-z | | 5(y-4)/3=2y-2 | | 3-5n=12 | | 156-7x=20x+24 | | X+3=(Y+3)*2 | | 6m^2-28m-48=0 | | -2(x-7)-140=5x-7(x+8) | | -n+6=-(n-8) |

Equations solver categories